2021
DOI: 10.3390/ani11113113
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire Study on the Use of Complementary and Alternative Veterinary Medicine for Horses in Sweden

Abstract: Complementary or alternative veterinary medicine (CAVM) includes treatment methods with limited scientific evidence. Swedish veterinarians are legally obliged to base treatments and recommendations on science or well-documented experience, but most CAVM methods are not well documented in animals. The aim of this study was to explore the use of CAVM in Swedish horses. Electronic questionnaires were distributed to horse owners, equine veterinary practitioners and CAVM therapists. Of the 204 responding horse owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…A New Zealand study shows that 26% of dressage riders use different types of massage for their horses and the main indication for using allied health personnel to treat their horse was back problems [ 7 ]. The same results are shown in a Swedish study, indicating that massage is predominantly used for back and muscle problems in horses [ 8 ]. Further, an international study, asking equine veterinarians what rehabilitation modality they used, stated that 83% of the respondents used stretching and 69% used massage [ 9 ].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…A New Zealand study shows that 26% of dressage riders use different types of massage for their horses and the main indication for using allied health personnel to treat their horse was back problems [ 7 ]. The same results are shown in a Swedish study, indicating that massage is predominantly used for back and muscle problems in horses [ 8 ]. Further, an international study, asking equine veterinarians what rehabilitation modality they used, stated that 83% of the respondents used stretching and 69% used massage [ 9 ].…”
Section: Introductionsupporting
confidence: 78%
“…Soft tissue mobilization can be conducted by trained professionals, but it is also performed by laypeople and animal owners. Studies have shown that massage is commonly used both in companion animals and in sport horses [ 6 , 7 , 8 , 9 ]. A study on Swiss warmblood horses reports massage to be used in 8% of the horses treated for lameness and back problems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Swedish horse owners [24], Swedish dog owners seem to rarely use CAVM for their dogs, but the same methods (massage and stretching) appear to be the most common. This was mostly a reflection of the methods preferred by CAVM therapists, although the ranking of methods such as acupressure and laser therapy differed somewhat between dog owners and therapists.…”
Section: Discussionmentioning
confidence: 93%
“…The study was performed as an MSc project at the Swedish University of Agricultural Sciences [23], in parallel to a similar project on horse owners and equine veterinary practitioners [24]. Electronic questionnaires were constructed and distributed to dog owners, small animal veterinary practitioners, and CAVM therapists as described in Gilberg et al [24], and the therapist questionnaire was the same as in that study. Briefly, the dog owner questionnaires were distributed via social media, and the questionnaires for veterinarians and therapists were distributed via professional organisations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation